Public accounting in México and Sonora - Gracida Romo, Juan José (Universidad de Sonora, 2018)
The development of accounting as a profession is in line with the demand of the regions and their types of business in an evolution shared with the national and regional economic plan. In this work, it presents the emergence, development and evolution of the accounting in the country, and the state of Sonora, through a historiographic study, result of an exhaustive work of historical sources, interviews and iconographic consultation of events Various related, forming part of a research project of history of accounting between two institutions: the National Institute of Anthropology and History and the University of Sonora.